Damage Simulation Study of Composite-to-Metal Interference-Fit with Multiple Structural Parameters - Shan Jiang; Xiao Guo; Rui Zhao; Dongxu Zhang; Min Wan (Crystals)
Composite-to-metal interference-fit is widely used in the aerospace field, where the problem of the damage and failure of composite materials is particularly critical. A numerical study was conducted on the damage and failure of carbon fiber composite sleeves with multiple structural parameters during interference-fit assembly. ABAQUS/Explicit simulation of interference-fit was performed with the three-dimensional finite element method, and the VUMAT subroutine with three-dimensional Hashin damage was utilized to investigate the initiation and evolution of composite component damage. The effects of different relative wall thicknesses and layup sequences on the selection of maximum interference were analyzed. The results reveal that the stress distribution on the inner surface of the sleeve is more uniform with the condition of radial layup. Radial layup enables 0.2% interference at 25% wall thickness, a 100% increase over axial layup. This study contributes to addressing long-standing issues in the aerospace field, such as connection failure and insufficient fatigue life. It is of great significance for improving structural performance, reducing costs, and promoting technological innovation.